2015
DOI: 10.1056/nejmcpc1409840
|View full text |Cite
|
Sign up to set email alerts
|

Case 8-2015

Abstract: Pr esentation of C a seDr. Naina Rastalsky (Medicine): A 68-year-old man with multiple myeloma was seen in the rheumatology clinic of this hospital because of increasing skin tightness, joint pain, and swelling of the hands and feet.The patient had been well until 2 years before this presentation, when anemia was noted on routine examination at another hospital. During the next 7 months, endoscopic and colonoscopic screening examinations were negative. Pathological examination of a bone marrow-biopsy specimen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Wigley et al [ 56 ] reported a case of SSc presenting with SRC in a 68-year-old man with MM who had been treated and had entered remission.…”
Section: Association Of Ssc With Malignancymentioning
confidence: 99%
“…Wigley et al [ 56 ] reported a case of SSc presenting with SRC in a 68-year-old man with MM who had been treated and had entered remission.…”
Section: Association Of Ssc With Malignancymentioning
confidence: 99%